The Effect of Career Mentoring on Employment Outcomes for College Students who Are Legally Blind. (September 2016) - O'Mally, Jamie; Antonelli, Karla
Introduction: College graduates with visual impairments (that is, those who are blind or have low vision) often face challenges in securing competitive employment after graduation. Working with a mentor who is also visually impaired, and working in the same field, can provide important benefits to overcome these barriers. Methods: A nationwide longitudinal study, involving random assignment to an intervention group working with a mentor or a comparison group given traditional career resources, evaluated changes in job-seeking self-efficacy, assertiveness in job hunting, and career adaptability over the course of one year as legally blind college students prepared to graduate and enter the job market. Employment outcomes, job satisfaction, and evaluation of the mentoring program were also measured. Results: Those working with mentors demonstrated increased job-seeking self-efficacy, career adaptability, and significant gains in assertiveness in job-hunting compared to those receiving only traditional job-search resources. Although no significant differences were found between groups for employment rate or job satisfaction, participants reported high satisfaction with the program. Discussion: Working with a mentor demonstrated positive trends for self-efficacy, career adaptability, and significant increases in job-hunting assertiveness among visually impaired college students with legal blindness. Participants were highly committed and found the program beneficial. Small sample size may have limited the ability to detect significant differences in employment outcomes.